A clinical and microbiological study of puerperal sepsis in a tertiary care hospital in India. (18th June 2019) - Vanukuru, Jayasree; Bagga, Rashmi; Muthyala, Tanuja; Gautam, Vikas; Sethi, Sunil; Jain, Vanita; Sikka, Pooja
Abstract: Objective: This prospective study was carried out to evaluate the clinical profile and bacterial isolates among women with puerperal sepsis in a tertiary hospital in North India. Materials and methods : Women with puerperal sepsis ( n = 45) admitted from January 2015 to April 2016 were followed prospectively. Cultures were obtained from cervix, blood, urine, and pyoperitoneum. Initial antibiotics were cefotaxime or piperacillin with tazobactam plus amikacin plus clindamycin or metronidazole and were changed according to sensitivity. Results : Out of 7887 deliveries during this period, 45 (0.2%) women had puerperal sepsis. 16 (35.5%) delivered in the present hospital, 25 (55.5%) at another health care facility, and 4 (8.9%) at home. Delivery was by cesarean section (CS) in 24/45 (53.3%) and vaginal in 21/45 (46.6%). Grade 1 sepsis occurred in 21, grade 2 in two, and grade 3 in 22 women. Majority (29/45 or 64.5%) had no risk factor for puerperal sepsis. There were two (4.4%) deaths and 13/45 (28.8%) had near-miss morbidity. Pathogenic bacteria were isolated in 33/45 (73.3%) in cervical swab (69%), blood, urine, or pus culture with no significant difference in the bacterial yield or species isolated between cotton or polyester swabs ( p > .05). Escherichia coli were the commonest isolate and was sensitive to amikacin in all. Five had stillbirths and 4/40 neonates developed sepsis but recovered. Conclusions : Escherichia coli was the commonest pathogen and was uniformly sensitive to amikacin, which may be included among the initial antibiotics to treat puerperal sepsis in India.